THE PRACTICE OF MOTHER WITH HIV/AIDS IN ORDER TO PREVENT INFECTION TRANSMISSION TO THE CHILD - Ernawati Ernawati; Siti Aisah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction: HIV/AIDS as problems not only for adult, but these epidemic direct and indirect influence at children and families. Since 2005 UNICEF others seizing the initiate to against campaign with programedprevention of mother to child transmission of HIV (PMTCT). Purpose of the research to exploration practice of mother HIV/AIDS positive to prevention infection to child. Located of the research in Kudus regency Central Java. Methods: Qualitative research methods by case studies conducted In-depth interviews on twelve HIV-positive mothers werepurposively selected. The triangulation to a case manager of HIV/AID and families. Data processing used manual of the thematic content analysis. Results: The results found after diagnosed HIV status, mother's good practices as sexual safe practice, Condom used, preventive pregnancies caused psychological trauma. ART consumtive since 26 weeks of gestation for preventive infection to child. Discussion:Most of them have families support, but stigmaanddiscrimination by health provider and public government. Keywords: HIV/AIDS, PMTCT, Preventive practice